Research on mobile stroke unit based on 5G network technology - Yu SHENG; Zhiheng LIU; Liya SHAN; Yi FENG (Dianxin kexue)
The 5G mobile stroke unit uses advanced next-generation information and communication technologies such as the Internet of things,mobile Internet,cloud computing,5G,etc.,to connect and achieve healthy interaction with people,equipment,and resources related to health care,which can guarantee people's timely access to preven-tive and therapeutic medical services.The composition design,functional modules,implementation architecture,and innovative service models of 5G mobile stroke units were discussed.The combination of 5G network technology and mobile stroke units were analyzed,and the network requirements of 5G mobile stroke units was analyzed with spe-cific cases.